Plastidial Phosphoglucose Isomerase Is an Important Determinant of Seed Yield through Its Involvement in Gibberellin-Mediated Reproductive Development and Storage Reserve Biosynthesis in Arabidopsis. Issue 9 (10th August 2018) - Bahaji, Abdellatif; Almagro, Goizeder; Ezquer, Ignacio; Gámez-Arcas, Samuel; Sánchez-López, Ángela María; Muñoz, Francisco José; Barrio, Ramón José; Sampedro, M. Carmen; De Diego, Nuria; Spíchal, Lukáš; Doležal, Karel; Tarkowská, Danuše; et al.
Abstract : Plastidial phosphoglucose isomerase determines seed yield by affecting gibberellin-mediated reproductive development and the conversion of glucose-6-phosphate to seed fatty acids and proteins. Abstract: The plastid-localized phosphoglucose isomerase isoform PGI1 is an important determinant of growth in Arabidopsis thaliana, likely due to its involvement in the biosynthesis of plastidial isoprenoid-derived hormones. Here, we investigated whether PGI1 also influences seed yields. PGI1 is strongly expressed in maturing seed embryos and vascular tissues. PGI1- null pgi1-2 plants had ∼60% lower seed yields than wild-type plants, with reduced numbers of inflorescences and thus fewer siliques and seeds per plant. These traits were associated with low bioactive gibberellin (GA) contents. Accordingly, wild-type phenotypes were restored by exogenous GA application. pgi1-2 seeds were lighter and accumulated ∼50% less fatty acids (FAs) and ∼35% less protein than wild-type seeds. Seeds of cytokinin-deficient plants overexpressing CYTOKININ OXIDASE/DEHYDROGENASE1 (35S:AtCKX1) and GA-deficient ga20ox1 ga20ox2 mutants did not accumulate low levels of FAs, and exogenous application of the cytokinin 6-benzylaminopurine and GAs did not rescue the reduced weight and FA content of pgi1-2 seeds. Seeds from reciprocal crosses between pgi1-2 and wild-type plants accumulated wild-type levels of FAs and proteins. Therefore, PGI1 is an important determinant of Arabidopsis seed yield due to its involvement in two processes: GA-mediated reproductive development and the metabolic conversion of plastidial glucose-6-phosphate to storage reserves in the embryo.